2-N-Anilinopurine, 2- N-Piperidinopurine, 2-N-Phenylalaninopurine and 2-N- Prolinopurine: fluorescence characteristics - Abdullah, Z.; Shariffuddin, M.A.M.; Bakar, N.K.A.; Idris, A.M. (2007)
2-N-Anilinopurine, 2-N-Piperidinopurine, 2-N-Phenylalaninopurine and 2-NProlinopurine were obtained when 2-fluoropurine was reacted with aniline, piperidine, phenylalanine and proline respectively. The structures of all the compounds were confirmed by infrared, 1H NMR and mass spectrometries. The fluorescence characteristics of these 2-substituted purines were studied in 75 ethanol. 2-N-Anilinopurine showed the highest fluorescence intensity followed by 2-N-Piperidinopurine, 2-N-Phenylalaninopurine and 2-N-Prolinopurine showed the least intensity. 2-N-Anilinopurine, 2-N-piperidinopurine and 2-N-phenylalaninopurine were excited at 340 nm and the fluorescence peaks were observed at 473, 490 and 490 nm respectively, while 2-prolinopurine was excited at 385 nm, and fluoresced at 470 nm.